Finite element modeling method of centrifugal rotary processing - A. N. Soloviev; M. A. Tamarkin; Nguyen Van Tho (Advanced Engineering Research, 2019)
Introduction. In modern production, when performing finishing operations, centrifugal rotary processing in the medium of abrasive plays an important role. High productivity, low costs and extensive technological capabilities are the main advantages of these cleaning and finishing operations. This paper considers the process of abrasive particle – workpiece surface interaction within the framework of the static contact problem of the elasticity theory. Thus, plastic deformation in the contact area comes into account.Materials and Methods. The abrasive particle (corundum) is simulated with a linearly elastic body, whose Young's modulus is significantly larger than that of the work material. The process material (steel) is simulated with an elastoplastic bilinear body using the von Mises yield criterion.Research Results. Finite element modeling of the structures under consideration was performed in the ANSYS CAE package. The process of abrasive particle – workpiece surface interaction was simulated; its stress-strain state was analyzed. The results of numerical experiments are presented. They have determined how equivalent plastic strains are distributed at depths of the cone penetration of 0.01 mm and 0.05 mm. The data obtained, as well as the areas of plastic strain values of more than 1%, are visualized in the ANSYS CAE package.Discussion and Conclusions. It is established that the equivalent plastic deformation is proportional to the depth of penetration (DP). It reaches a minimum value of 0.158 at DP = 0.01 mm, and a maximum of 0.825 at DP = 0.05 mm. The dependences of the plastic region sizes on DP are determined for cases when the plastic deformation exceeds 1%. At the maximum penetration (0.05 mm), the deformation radius is 1 mm, and the depth is 0.8 mm. On the basis of the data obtained as a result of the conducted research, the parameters of the technological process (rotational speed, size of the abrasive surface, mass of abrasive particles) that affect the workpiece – abrasive particle interaction can be selected. A judicious choice of these parameters will increase the processing efficiency